2022
DOI: 10.1186/s12912-022-01119-2
|View full text |Cite|
|
Sign up to set email alerts
|

Authoritarian leadership and nurse presenteeism: the role of workload and leader identification

Abstract: Background Nurses’ health in the workplace is crucial for ensuring the quality of healthcare. However, presenteeism, the behavior of working in a state of ill health, is widespread in the nursing industry. Considering that the origin of authoritarian leadership and the prevalence of presenteeism are inseparable from Chinese workplace culture, this study aimed to explore the impact and mechanism of authoritarian leadership on presenteeism. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
2
13
0
1
Order By: Relevance
“…Therefore, understanding the workplace factors that may encourage presenteeism is important (e.g. Dietz et al, 2020;Huang et al, 2021;Shan et al, 2022;Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, understanding the workplace factors that may encourage presenteeism is important (e.g. Dietz et al, 2020;Huang et al, 2021;Shan et al, 2022;Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, scholars have examined the impact of leadership presenteeism (Dietz et al, 2020), supervisor support behaviors (Schmid et al, 2017), and leadership stress (Dietz and Scheel, 2017) on employee presenteeism. Recent work has also examined health promotion leadership (Shan et al, 2022), inclusive leadership (Qian and Wang, 2022), authoritative leadership (Shan et al, 2022), and the leader-subordinate relationship (LMX) (Huang et al, 2021;Wu et al, 2023). These studies mainly draw on cognitive mechanisms such as social learning mechanisms (Dietz et al, 2020;Shan et al, 2022), stress perception, psychological security (Schmid et al, 2017;Qian and Wang, 2022), social exchange (Huang et al, 2021;Lu et al, 2013;Wu et al, 2023) and resource conservation to explore leadership factors' influence on presenteeism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 2,291 nurses demonstrated that nurses' better perception of their work environment was related to a higher evaluation of the head nurses' leadership [28]. An overly authoritative leadership style can lead to more serious presenteeism [29]. Nurses' presenteeism may prevent them from fully engaging in their work, eventually leading to false job embeddedness [27].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the order of the 3rd affiliation and the 4th affiliation should be exchanged. The correct author affiliations have been provided in this Correction.…”
mentioning
confidence: 99%